Spanish regional unemployment revisited: The role of capital accumulation - Roberto Bande; Marika Karanassou (Institute for the Study of Labor (IZA), 2010)
This paper provides new evidence for the evolution of regional unemployment rates in Spain over the 1980-2000 period. We argue that interactive dynamic systems of labour demand, wage setting, and labour force equations (i) allow for a richer interpretation of regional disparities, and (ii) can capture the unemployment effects of growing variables such as capital stock. After classifying the 17 Spanish regions into high and low unemployment groups using kernel and cluster techniques, we estimate a structural labour market model for each group and evaluate the unemployment contributions of investment, benefits, taxes, and the oil price. We find that the main driving force of regional unemployment swings is capital accumulation.
Keywords: R23; J64; 330; Regional unemployment; disparities; capital accummulation; kernel; cluster; Regionale Arbeitslosigkeit; Investition; Regionaler Arbeitsmarkt; Arbeitsnachfrage; Schätzung; Spanien